Study of antibiotic resistance in bacteria Isolated from table egg - ASHISH KR. JAIN; RAJESH YADAV (International Journal of Pharma and Bio Sciences, 2017)
A total of 132 egg samples were collected from different areas of Jaipur, India. Gram negative enterobacteria were isolated initially on Nutrient agar and then on selective-differential media and further characterized by different biochemical tests. Commonly prescribed antibiotics in patients for gastro-intestinal infection were used for antibiotic susceptibility test. Against different antibiotics different resistance pattern were found (p<0.01). The highest resistance rate were detected against Cefixime (86.66%) whereas highest sensitivity rate (100%) were recorded against Gentamicin, Levofloxacin and Ciprofloxacin. Also, most of the isolates (73.3%) were found to be multi drug resistant as these showed resistance against three or more antibiotics tested. Multiple antibiotic resistance index of isolated microbes from table egg ranged from 0.10 to 0.70. It can be concluded that commercial eggs which are consumed as food may harbour multi-drug resistant bacterial pathogens and if consumed raw may cause severe ailments in consumers. Antibiotic resistance of bacterial species will make the clinical treatment of diseases more difficult. Thus aim of the present study is to assess the risk of antibiotic resistance in table eggs and egg products.